DRIVING PURCHASE BEHAVIOR IN SOCIAL COMMERCE: THE ROLE OF INNOVATION, ENGAGEMENT, TRUST, AND PERCEIVED VALUE - Husnil Khatimah; Fairol Halim; Annas Osman Ali Eltahir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Social commerce has rapidly transformed consumer behavior by combining technological innovation and social engagement. This study investigates the effect of social commerce innovation on consumer behavior using an extended Theory of Planned Behavior (TPB) framework, including customer engagement, brand trust, and perceived value. Data from 360 active social commerce users in Padang, Indonesia were collected via purposive sampling using an online structured questionnaire and analyzed using PLS-SEM. Results show that social commerce innovation significantly affects attitude, subjective norms, and perceived behavioral control, while marketing constructs mediate the relationship with behavioral intention. Attitude is the strongest predictor of intention, followed by subjective norms and perceived behavioral control, and behavioral intention strongly predicts actual purchasing behavior, confirming the robustness of the extended TPB model. The study provides a theoretical contribution by integrating innovation-driven marketing constructs into TPB and offers practical guidance for enhancing platform innovation, engagement, trust, and perceived value. Future research may examine moderating factors such as demographics, cultural differences, and AI personalization